2019
DOI: 10.1158/0008-5472.can-18-1785
|View full text |Cite
|
Sign up to set email alerts
|

Selective EGLN Inhibition Enables Ablative Radiotherapy and Improves Survival in Unresectable Pancreatic Cancer

Abstract: The EGLN inhibitor FG-4592 reduces radiation toxicity to the GI tract, which enables definitive radiation treatments for pancreatic cancer.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 45 publications
0
21
0
Order By: Relevance
“…However, recent studies showed an antitumor action of FG-4592 in macrophage-abundant tumors ( Nishide et al., 2019 ), and in human ovarian clear cell carcinoma ES2 cells ( Price et al., 2019 ). In another study, FG-4592 could selectively protect the intestinal tract from radiation toxicity without affecting pancreatic cancer ( Fujimoto et al., 2019 ). In our present study, we treated DOX-sensitive cells of HepG2 and MCF-7 with FG-4592 in combination with DOX for 24 h and found FG-4592 had no further effect on the reduced cell viability induced by DOX.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies showed an antitumor action of FG-4592 in macrophage-abundant tumors ( Nishide et al., 2019 ), and in human ovarian clear cell carcinoma ES2 cells ( Price et al., 2019 ). In another study, FG-4592 could selectively protect the intestinal tract from radiation toxicity without affecting pancreatic cancer ( Fujimoto et al., 2019 ). In our present study, we treated DOX-sensitive cells of HepG2 and MCF-7 with FG-4592 in combination with DOX for 24 h and found FG-4592 had no further effect on the reduced cell viability induced by DOX.…”
Section: Discussionmentioning
confidence: 99%
“…Orthotopic pancreas injection. Orthotopic pancreatic injections were performed as previously described (49). Before surgery, animals were shaved around the surgical site to remove excess fur; 0.1 mg/kg extended release buprenorphine was given as an analgesic.…”
Section: Methodsmentioning
confidence: 99%
“…HIF-1a, the master regulator of hypoxia, modulates pathways that are vital to PDA carcinogenesis and has been correlated with poor patient survival (22)(23)(24)(25)(26). While the pro-tumorigenic effect of hypoxia in PDA cannot be contended, some studies have highlighted a tumor suppressor role for HIFs, implicating them in having a protective function against tumor formation (27)(28)(29)(30). It is important to note that such studies have focused on epithelial HIF expression, giving little credit to the impact of HIF signaling within the TME (31).…”
mentioning
confidence: 99%